The Health Impact of Cocoa from Cultivation to the Formation of Biogenic Amines: An Updated Review - Antonello Paparella; Maria Schirone; Clemencia Chaves López (Foods)
Cocoa and chocolate are known for their health benefits, which depend on factors like cocoa variety, post-harvest practices, and manufacturing processes, including fermentation, drying, roasting, grinding, and refining. These processing methods can influence the concentration and bioavailability of bioactive compounds, such as polyphenols that are linked to cardiovascular health and antioxidant effects. Recent scientific research has led to the development of cocoa-based products marketed as functional foods. However, despite the growing interest in the functional potential of cocoa, the literature lacks crucial information about the properties of different varieties of cocoa and their possible implications for human health. Moreover, climate change is affecting global cocoa production, potentially altering product composition and health-related characteristics. In addition to polyphenols, other compounds of interest are biogenic amines, due to their role and potential toxic effects on human health. Based on toxicological data and recent research on the complex relationship between biogenic amines and cocoa fermentation, setting limits or standards for biogenic amines in cocoa and chocolate could help ensure product safety. Finally, new trends in research on biogenic amines in chocolate suggest that these compounds might also be used as quality markers, and that product formulation and process conditions could change content and diversity of the different amines.